BODY POSITIVITY VS. BODY IDEAL: STUDI KASUS PENGARUH KONTEN TIKTOK PADA CITRA TUBUH GENERASI Z - Aliyah Agita Artamevia (Jurnal Sosiologi UPR, 2025)
This study examines the influence of TikTok content on Generation Z's body image, focusing on two main concepts: body positivity and body ideal. The study employs a descriptive-analytic qualitative method with a case study approach, observing TikTok-related content through documentation, observation, and literature review techniques. The findings reveal that while the body positivity movement on TikTok has positive effects, such as encouraging self- acceptance and body diversity, the body ideal narrative promoting unrealistic beauty standards remains dominant. This creates tension for Generation Z in understanding and accepting their body image. The study highlights the importance of digital literacy and more inclusive platform algorithms to create a healthy and diverse social media environment.